Service Leadership Strategy to Motivate and Improve Employee Performance at Primaya Hospital Bekasi - Muttaqin, Nurhanifah Zainum (Lentera Ilmu Nusantara, 2024)
This abstract discusses the research conducted at Primaya Hospital Bekasi on the influence of leadership style, motivation, and work discipline on the performance of employees in the organization. This study uses qualitative research methods with a case study approach. The results showed that a leadership style focused on service had a greater contribution compared to employee motivation in direct measurement of performance. However, these two factors are interrelated and can influence each other. The implementation of strong leadership strategies can increase employee motivation, which in turn also contributes to overall performance. This study also shows that work discipline plays a very important role in the performance of employees' work. By managing these elements well, organizations can achieve their goals, maintain quality of service, and compete effectively in a rapidly changing environment. In conclusion, leadership style, motivation, and work discipline can have an effect on employee performance in an organization. By managing these elements well, organizations can achieve their goals, maintain quality of service, and compete effectively in a rapidly changing environment.